Oral Administration of a Shigella 2aT32-Based Vaccine Expressing UreB-HspA Fusion Antigen With and Without Parenteral rUreB-HspA Boost Confers Protection Against Helicobacter pylori in Mice Model - Zhang, Xin; Sang, Shuli; Guan, Qing; Tao, Haoxia; Wang, Yanchun; Liu, Chunjie (Frontiers in Immunology, 2022)
Helicobacter pylori (H. pylori) is a gram-negative pathogen classified as a class I carcinogen. The H. pylori urease B subunit (UreB) and heat shock protein A (HspA) are two important vaccine candidate antigens. In this study, we evaluated the immunogenicity and immunoprotective effect of the attenuated Shigella vector vaccine SH02 expressing the UreB-HspA fusion protein of H. pylori in a mouse model. Oral SH02 with or without subcutaneous injection of rUreB-HspA induced antigen-specific serum IgG, mucosal sIgA, and T cells immune response. Subcutaneous injection of the candidate antigen rUreB-HspA enhanced the level of serum antigen-specific IgG antibodies (p < 0.0001) and the levels of IgG1/IgG2a/IgG2b subtypes. In addition, injection boost also increased the proportion of spleen antigen-specific CD4+CD154+ T cells (p < 0.001), and the proportion of CD4+CD154+ T cells that secrete IFN-γ and IL-17A. Following the H. pylori challenge, the levels of H. pylori colonization in the two experimental groups (Groups A and B) significantly reduced compared with the control group (p < 0.001), indicating that the candidate vaccine yielded a preventive effect of anti-H .pylori infection. Compared with the non-subcutaneous booster injection group (Group A), the subcutaneous booster injection group (Group B) exhibited less gastric inflammation, but there was no significant difference in the level of colonization (p > 0.05). These results lay a foundation for the development of a vaccine against H. pylori and the optimization of immunization methods and procedures to prevent H. pylori infection.